2007
DOI: 10.1111/j.1365-2141.2007.06502.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained anaemia in older persons is characterised by low erythropoietin and low levels of pro‐inflammatory markers

Abstract: SummaryEpidemiological studies report that a third of the cases of anaemia in older persons is unexplained. We compared erythropoietin (EPO), inflammatory markers and major comorbidities between older subjects with normal haemoglobin levels and those with different aetiologic forms of anaemia, including unexplained anaemia. Participants were a representative sample of 964 persons aged ≥65 years, with no evidence of bleeding, complete blood tests, and a complete blood count within 6 h of phlebotomy. Anaemia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 30 publications
6
102
1
2
Order By: Relevance
“…The observation of a direct association between donor age and Hb levels, independent of graft function, clearly suggests an age-related influence on the erythropoietin production capacity of the kidney. Although frequently hypothesized in the past, it has been shown only recently that anemia of unknown origin in the elderly might be caused by lower than normal erythropoietin levels [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of a direct association between donor age and Hb levels, independent of graft function, clearly suggests an age-related influence on the erythropoietin production capacity of the kidney. Although frequently hypothesized in the past, it has been shown only recently that anemia of unknown origin in the elderly might be caused by lower than normal erythropoietin levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and ninety-one of these 215 units (89%) were administered during the initial hospitalization. The first unit was administered on day 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The level of Hb triggering transfusion was 8.0 ± 0.8 g/dl.…”
Section: Anemia Management Therapy In the Immediate Post-transplant Pmentioning
confidence: 99%
“…18 Further, approximately one-third of anemia cases are not explained by nutrient deficiencies (iron, B12, or folate), renal insufficiency, or chronic inflamma- tion. [18][19][20] Although some of these cases might result from myelodysplastic syndrome, Guralnik and colleagues estimated that at least one-quarter of the anemia cases in older adults would remain unexplained. 18 While erythropoietin levels have been shown to increase with aging, 8 suggesting that decreased bone marrow response or red cell survival contributes to anemia in older adults, Ferrucci and colleagues demonstrated that erythropoietin levels and pro-inflammatory cytokines were significantly lower in older Italian adults with unexplained anemia compared to non-anemic persons.…”
mentioning
confidence: 99%
“…18 While erythropoietin levels have been shown to increase with aging, 8 suggesting that decreased bone marrow response or red cell survival contributes to anemia in older adults, Ferrucci and colleagues demonstrated that erythropoietin levels and pro-inflammatory cytokines were significantly lower in older Italian adults with unexplained anemia compared to non-anemic persons. 20 The genetic contribution to unexplained anemia in older adults has not been defined. In view of the high prevalence of anemia in older adults and its association with adverse outcomes, an expanded research effort into the role of genetics in hemoglobin variability and anemia in older adults is warranted.…”
mentioning
confidence: 99%
“…35 EPO levels are, however, unexpectedly suppressed in anemic elderly patients when compared with anemic young individuals, which suggests a blunted response to low hemoglobin levels. [36][37][38] Older women with osteoporosis and mild renal dysfunction exhibit lower calcium absorption rates and lower serum 1,25-dihydroxyvitamin D levels despite normal serum 25-hydroxyvitamin D levels, indicating a deficiency in the conversion of 25-hydroxyvitamin D to 1,25-dihydroxyvitamin D by the aging kidneys. 39 Mild renal dysfunction (creatinine clearance less than 65 ml min À1 ) is an independent risk factor for falls and their associated fractures in older patients with osteoporosis.…”
Section: Endocrine Functionmentioning
confidence: 99%